2018
DOI: 10.2478/auoc-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition of raw and cooked Rapana venosa from the Black Sea

Abstract: Rapana venosa is an edible mollusc with nutritional and economic importance. There is limited information about its lipid composition. The aim of the present study is to provide information about lipid composition, fatty acid profiles, fat soluble vitamins and cholesterol content of raw and cooked Rapana venosa. Cooking did not affect the ratio of lipid classes, but fatty acids composition varied significantly. Considerable variations were observed in fatty acid distribution of total lipids and neutral lipids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…It is a predatory marine snail that quickly expanded in the Black Sea, having a negative effect on the ecosystem, especially inducing the decline of different species of mussels and mollusks [21]. Besides its nutritional value [18,22], R. venosa is also appreciated as a potential source for biotechnological applications. Previous studies have reported that amino acids and lipids extracted from R. venosa exhibited wound-healing properties on rat skin burns [18,23].…”
Section: Introductionmentioning
confidence: 99%
“…It is a predatory marine snail that quickly expanded in the Black Sea, having a negative effect on the ecosystem, especially inducing the decline of different species of mussels and mollusks [21]. Besides its nutritional value [18,22], R. venosa is also appreciated as a potential source for biotechnological applications. Previous studies have reported that amino acids and lipids extracted from R. venosa exhibited wound-healing properties on rat skin burns [18,23].…”
Section: Introductionmentioning
confidence: 99%
“…Comparably low TL contents were found for the Black Sea R. venosa [ 55 ], and R. venosa from Qingdao seafood markets in China [ 56 ]. In our previous studies, R. venosa presented higher TL content (1.26 g.100 g −1 ww) [ 22 ] and lower TL values (0.5 g.100 g −1 ww) [ 57 ]. Information on C. crangon lipid composition is limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, in Bulgaria there is limited information regarding the n-3 LCPUFA contents in seafood products, traditionally preferred and consumed by the local population. Earlier studies reported data on the lipid and fatty acid composition of some Black Sea fish and shellfish species and showed that total lipid content and FA profiles, including PUFA levels, are species-specific [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Having in mind these facts, the aims of this study were to determine lipid content, omega-3 polyunsaturated fatty acids (EPA and DHA), and the recommended daily serving of eleven fish species, three bivalve species, one gastropod, and one crustacean species harvested from the Western part of the Black Sea, Bulgaria, and regularly available on the Bulgarian fish markets.…”
Section: Introductionmentioning
confidence: 99%
“…These are the maximum permissible values adopted in the Russian Sanitary Rules and Regulations (SanPiN, Cu: 30.0, Zn: 200.0, As: 2.0, Cd: 2.0, Hg: 0.2, and Pb: 10.0 mg•kg −1 w.w.) [56] and in the European Commission Regulation [57], contamination-indicative contents (CIC) of heavy metals in mollusks [58], and action levels established by the United States Food and Drug Administration [59]. The maximum permissible levels were transformed from the wet weight basis to the dry weight basis using the conversion factors: 6.29 for M. galloprovincialis [60], 4.18 for R. venosa [61], and 9.47 for C. gigas [62].…”
Section: Element Contents In Soft Tissues Of the Mollusksmentioning
confidence: 99%
“…Because food is commonly understood as a product ready for partaking, EDI should be calculated using the element content in the cooked form if cooking is relevant. In the cooked meat of the mussel and the sea snail, the factors of conversion from dry to wet weight are 3.45 and 3.82, respectively [60,61]. Oysters are typically consumed in raw form and the corresponding conversion factor is 9.47 [62].…”
Section: Assessment Of Human Health Risks From the Mollusk Consumptionmentioning
confidence: 99%